A photographic probe for wet steam - Vernon, Kris (2014)
The work carried out during this engineering doctorate degree has led to significant advances in the application of photographic measurement techniques to the characterisation of coarse water in wet steam flow, with particular emphasis on the development of a compact measurement probe suitable for application in a low-pressure steam turbine. Through the application of pulsed LED illumination for the first time in a compact probe, photographs at high magnification with excellent resolution are obtainable at significantly shorter exposure times than others reported in the literature. This has the advantage of reducing motion blur enabling reliable quantitative analysis to take place.